PENGARUH TINGKAT PERTUMBUHAN EKONOMI DAN TINGKAT PENDIDIKAN TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KABUPATEN LOMBOK TENGAH - Lale Ajeng Khalifatun Wardani; Hidayanti; Selamat Riadi; Baiq Rizka Milania Ulfah (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2024)
This research is entitled "The Influence of the Level of Economic Growth and Level of Education on the Level of Open Unemployment in Central Lombok Regency". In this research, researchers want to see how the level of economic growth and education level influence the level of open poverty in Central Lombok Regency in 2016-2022. This type of research is quantitative research with an associative approach. The analytical tool used in this research is multiple linear regression analysis. That partial economic growth has no significant effect on open poverty in Central Lombok Regency (Y). This can be seen from the value of Tcount (1.220) < Ttable (2.571) and the significance value of Tcount (0.290) > alpha significance (0.05). Education level (X2) has no significant effect on open poverty in Central Lombok Regency (Y). This can be seen from the calculated T value (0.093) < T table value (2.571) and can also be seen from the significance value, namely calculated significance 0.930 > alpha significance (0.05). Simultaneously, the estimation results show that the variables of economic growth and education level do not influence simultaneously, this is proven by the calculated F value < from F table (0.793 < 6.94). The results of the R-square test for the independent variable on the dependent variable, obtained a result or value of 0.533 with a significance value (α) or alpha of 0.05 (5%). The R-square value in this research has meaning, namely that the influence of the economic growth and education level variables is able to explain the open poverty level variable in Central Lombok Regency of 0.533 units or 53.3%, and this figure shows a small influence. Meanwhile, the remainder was influenced by other variables not included in this study, amounting to 46.7%.